The Impact of Various Types of Project-Based Teaching on the Guidance and Cultivation of Prosocial Behavior in University Students - Yu, Wenbin (Journal of Psychology and Psychotherapy Research, 2024)
Guiding and cultivating prosocial behavior in university students is a vital component of ideological and political education, as it is closely linked to the nation’s future and the overall moral fabric of society. This issue should be given due attention by university administrators. This study primarily employs literature review, teaching experiments, and statistical analysis methods to explore the differences in the impact of basketball project-based teaching (experimental group) and table tennis project-based teaching (control group) on the prosocial behavior of university students. A 16-week teaching experiment was conducted with 60 second-year students from two classes at Jiangxi University of Finance and Economics. The findings reveal that both the basketball and table tennis programs positively influenced prosocial behavior, though the effects varied across different dimensions of prosocial behavior. Overall, basketball project-based teaching proved to be more effective than table tennis in fostering and guiding prosocial behavior among university students.